Immunization - World Bank (Washington, DC, 2012)
Immunization deserves high priority, especially in developing countries, for three reasons: vaccine-preventable diseases, disproportionately affect the poorest fifth of the population; immunization is among the most cost-effective interventions, and has a major impact in reducing the burden of disease; and, newer vaccines - and those being developed - have the potential to prevent diseases, e.g., tuberculosis, malaria, HIVs. The reform of national health systems, should strengthen national immunization programs, and facilitate surveillance systems focused on routine immunization, without disregarding supplementary immunization campaigns, in order to achieve accelerated disease control initiatives. Furthermore, the note suggests the inclusion of the private sector, and nongovernmental organizations, as key participants in immunization coalitions for social mobilization, in public-private partnerships for vaccine research and development, and, in the provision of immunizations. Finally, the importance of reliable surveillance should be taken into account, to assess the overall impact of immunization systems, and identify outbreaks, areas of high-risk, and/or weak system performance.